Concepts and Practice of Humanitarian Medicine - Gunn, S. William A.; Masellis, Michele; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2008)
Concepts and Practice of Humanitarian Medicine Edited by S. William A. Gunn and Michele Masellis, International Association for Humanitarian Medicine, Switzerland As major events like war, epidemics, and climate change continue to push global health issues to the fore, the international medical community is called upon more than ever to address the needs of the most vulnerable. Concepts and Practice of Humanitarian Medicine brings public health and human rights concerns together, uniting medical, scientific, sociopolitical, and historical perspectives to reaffirm this vision. Forty-one essays from 33 international contributors set out the principles of humanitarian medicine, beginning with the concept of health as a human right, and examining topics such as quality of life, torture, and nuclear conflict. The book draws on important treaties and conventions throughout the history of the United Nations and the World Health Organization, and pays tribute to the efforts of individuals and organizations working to correct health inequities worldwide. A sampling of the topics: The potential of humanitarian medicine in torture prevention and intervention. The varied roles of international and nongovernmental agencies in humanitarian medicine. Critical issues specific to women, children, migrants, refugees, and the poor. Health effects in an increasingly nuclear world. Applications of humanitarian medicine in specialized areas such as heart surgery and trauma. Already acclaimed when first published as the pioneering book, Humanitarian Medicine, this new edition includes 14 additional thought-provoking chapters. The contributors are all major world figures in health and human rights, including Nobel Laureates Kofi Annan and Sir Joseph Rotblat. For those committed to the new health frontiers around the world—particularly researchers, professionals, social scientists, and policymakers in public health, global health, and human rights—Concepts and Practice of Humanitarian Medicine is both informative and empowering reading. Reviews of the first edition: "Challenging… Providing much food for thought. The prestigious authors add to the uniqueness of the publication." –WHO, Health Action in Crises "A galaxy of authors that includes three Nobel Laureates, two Secretaries-General of the United Nations, and two Directors-General of the World Health Organization promises a book of the highest interest. The result fully justifies the promise." –Journal of Humanitarian Medicine "A remarkable array of chapters of prime importance, and a complete view of the technical, philosophical, ethical, and humanist issues to inspire reflection." –Prof. Baron Michel Lechat, Centre de Rechèrches en Epidémiologie des Désastres, Belgium.
The Fundamentals: Human Rights and Health -- The Right to Health -- Health and Human Rights—A Public Health Perspective -- Health for All or Hell for All? The Role of Leadership in Health Equity -- The Declaration of Alma-Ata on Primary Health Care -- Health and Human Rights: In 25 Questions and Answers -- Freedom from Fear for Human Well-being: The Need for Humanitarian Medicine in the Prevention of Torture and the Treatment of its Survivors -- Humanitarian Medicine -- Humanitarian Medicine: A Vision and Action -- Ethical Principles for Everyone in Health Care -- Quality of Life and Medical Practice -- Medical Contributors to Social Progress: A Significant Aspect of Humanitarian Medicine -- Humanitarian Medicine Applied in a Highly Specialized Field: Cardiovascular Surgery -- Humanitarian Medicine for a Developing Country: Outreach to Cuba -- Humanitarian Basic Plastic Surgery -- International, UN and WHO Cooperation -- Find New Unity -- Health and Human Rights in International Legal Instruments -- The United Nations Today: Changes in Policies and Structures—The World Summit and UN Reform -- The Critical News Stories You Never Read -- United Nations Humanitarian Action and the Role of Non-governmental Organizations -- The UN Founding Fathers and Dr Chisholm -- Brock Chisholm—Doctor to the World -- The Language of International Humanitarian Action: A Brief Terminology -- Disasters and Conflicts -- Humanitarian Action in Major Emergencies -- The Humanitarian Postulate in Disaster Management -- Health and Social Issues of Migrants and Refugees -- Man-Conceived Disasters -- The Nuclear Issue and Pugwash -- Quantifiable Effects of Nuclear Conflict on Health and Society -- Avoidable Tragedy Post-Chernobyl—A Critical Analysis -- Science, Research and Perspectives -- The Role of Science to Improve the Quality of Life: Reflections on the Post-Genomic Era -- The Ethics of Research: The Responsibility of the Researcher -- The Cost of Not Doing Health Research -- Reflections on the Past, Present and Future of Medicine -- Scientists, Doctors and the Nuclear Dilemma -- Serving the Global Community Through eHealth: The Role of Academia -- Society, Health and Equity -- The Humanization of Medicine—A Religious Viewpoint -- Urban Social Exclusion—The Samusocial Response -- Social and Medical Progress Through Patient Education in Chronic Diseases -- An Equitable Society Protects the Health of its Weakest Members: Women and Children -- The Humanitarian Force of the UN Millennium Development Goals -- Science and the Health of the Poor -- Poverty and Disease—Health and Prosperity.
Keywords: Public health; Public Health